Improving Students’ Understanding of Qawāʿid Through A Snake And Ladders Game–Based Drill Approach - Nadatul Paujiyah; Odang Odang; Ade Arip Ardiansyah (Arabiyyatī: Journal of Arabic Language Education, 2025)
Learning Arabic grammar (qawaid) is often considered challenging for high school students due to its abstract nature and the use of monotonous teaching methods, which reduce motivation and learning outcomes. This study aims to investigate the effect of the drill method based on the Snake and Ladder game on improving students’ understanding of Arabic grammar and to compare its effectiveness with conventional methods. The research employed a quantitative approach with a quasi-experimental design involving two groups: an experimental group taught using the drill method with the game and a control group taught with traditional methods. The instruments used were observation, pretest and posttest, and documentation. Data was analyzed using a t-test to examine significant differences between the groups. The results revealed a significant improvement in the experimental group, with a posttest mean score of 86.29 compared to 63.38 in the control group. The N-Gain analysis indicated a moderate improvement category in the experimental group and a low category in the control group. This study contributes to highlighting the effectiveness of integrating educational games into drill-based learning as an engaging and impactful strategy to enhance students’ mastery of Arabic grammar.